RE-DESIGN KURIKULUM EKONOMI SYARIAH PERGURUAN TINGGI AGAMA ISLAM: - Nilam Sari (SCAD Independent, 2014)
The development of Islamic banking quantitatively, not supported by the availability of adequate human resources. Problems that occur at this time is the lack of reliable human resources in the field of Islamic economics, is a constraint that makes slowing economic development of Islam in Indonesia. Human intellectual capital plays an important role in driving the performance and competitiveness. Innovation in the financial industry in general and Islamic finance in particular requires the availability of expertise (expertise) and expertise (skills). Not only are the operational aspects, professionals also needed to support research and development in order to strengthen the capacity to innovate. Islamic University has a very important role in determining the future of Islamic Economics. If you see the future of Islamic economics, human resources required are those who not only understand the Islamic economic philosophy but also positive-normative-empirical. Two mastery must still be supported by the development of good character. The campus is not just a process of transfer of knowledge but also the transfer of character. Of course, this requires cooperation to establish all elements of the organizers of the college. Among the steps that can be done by universities in Indonesia in the development of Islamic economics, universities can standardize the curriculum of Islamic economics throughout Indonesia and curriculum development.